The Effectiveness of Indonesian Education Curriculum Reform on the Quality of Processes in Learning - Hetty M Pakpahan; Suherni Suherni; Lilis Pujiati; Rostiodertina Girsang (Jurnal Penelitian Pendidikan IPA, 2023)
UU no. 20 of 2003 aims to develop the potential of students in spiritual strength, noble character, intelligence, self-control, and the skills needed. To achieve this national education goal, the Government always seeks to improve the quality of education through educational curriculum reform, with the aim of improving and developing the previous curriculum. This can be seen from the frequent curriculum changes in Indonesia since 1947, 1964, 1968, 1973, 1975, 1984, 1994, 1997, 2004, 2006, 2013 curriculum, until now the era of the industrial revolution 5.0 is known as the independent curriculum. However, curriculum reform often creates problems among the school community and the general public. The problems that arise are how it is implemented and the reasons behind the curriculum change, and whether curriculum reform has an effect on the quality of learning? The quality of education and learning must be aligned with the process standards in article (1) of Government Regulation No. 19 of 2005 concerning National Standards Education that must be developed in the implementation of learning in educational units to achieve competence. To achieve learning competencies in the 5.0 industrial revolution era, 21st century skills are needed, namely critical thinking skills, communication skills. creativity and innovation, capable of collaboration. In addition, so that learning objectives can improve the quality of learning, attitudes and abilities must be possessed: mastering the current curriculum and learning tools, mastering material in the field of study, mastering assessment methods and techniques, commitment or love of the teacher to the task, and discipline